The Effect of Murottal Al-Qur'an Therapy on Academic Stress Among University Students - Radi Ubaidillah; Anita; Nadia Safana; Azzahra Julia Nadia; Audri Medina; Auryn Rahma Fakhirah Kimi (Journal of Islamic Psychology and Behavioral Sciences, 2025)
This study aims to see the influence between murottal Al-Qur'an with academic stress on students of the Faculty of psychology UIN Raden Fatah Palembang. Stress can affect anyone, including students. The importance of efforts to overcome academic stress for students is very influential on the ability of students to build and maintain physical and psychological conditions during learning. Subjects in this study are students of semester 5. This type of research is an experiment with the research design used is one group post-test pre-test. The results of the hypothesis show the significance value of 0.805 which sign value is greater than 0.05 then it can be concluded that there is no relationship between Murrotal Al-Qur'an to academic Stress in students.